2002
DOI: 10.1016/s0014-5793(02)02505-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of precursor cleavage at the dibasic sites

Abstract: The presence in the PP P 1 position relative to the LysArg doublet of either Phe, Tyr or Trp residues affects only pro-OT/Np(7^15) flexibility. This has a measurable effect on the dynamics of the peptide. Since the same modifications have a major influence on the K m and V max values of the peptide cleavage, these kinetic parameters should depend on the peptide substrate motions. Therefore, the primary kinetic contribution of substrate cleavage should arise from substrate dynamics rather than from the enzyme. ß Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…6). [64] Prosomatostatin and its derivatives Somatostatin is a 14-amino acid peptide widely distributed in the central nervous system and peripheral tissues in which it has diverse physiological actions. This peptide acts as a neuromodulator or a neurotransmitter in the central nervous system, as a regulatory hormone in the gastrointestinal tract and pancreas and as a release inhibitor of growth hormone and thyroid stimulating hormone in the pituitary [76].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6). [64] Prosomatostatin and its derivatives Somatostatin is a 14-amino acid peptide widely distributed in the central nervous system and peripheral tissues in which it has diverse physiological actions. This peptide acts as a neuromodulator or a neurotransmitter in the central nervous system, as a regulatory hormone in the gastrointestinal tract and pancreas and as a release inhibitor of growth hormone and thyroid stimulating hormone in the pituitary [76].…”
Section: Resultsmentioning
confidence: 99%
“…Since those OT/Np(7-15) peptide analogs were shown to be characterized by the same conformation, the dynamics of substrates must therefore play a role in modulating their proteolysis. So, the plasticity and peptide motions of OT/ Np(7-15) peptides, bearing Phe, Tyr, and Trp amino acid residues at the P 0 1 position, were evaluated by measuring the fluorescence properties of these aromatic residues [64]. As shown in Fig.…”
Section: Role Of Substrate Dynamics In the Kinetics Of The Dibasic CLmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, this group showed that introduction of a b-turn breaker into the proposed turn region abolishes the enzyme-substrate interaction [242]. Moreover, they state that the flexibility of the peptide substrate is necessary for the interaction [242,245].…”
Section: Peptide-derived Inhibitorsmentioning
confidence: 99%